2017
DOI: 10.1002/ca.22986
|View full text |Cite
|
Sign up to set email alerts
|

Vascular configurations of anastomotic basket of conus medullaris in human spinal cord

Abstract: The arterial basket of the conus medullaris is one of several anastomoses between the anterior and posterior spinal arteries. The anatomy of this structure has attracted little attention. This work sought to investigate its configuration in human spinal cords. Spinal cords from male and female cadavers (n = 32) were injected with colored latex through the intercostal, lumbar, medial sacral and the posterior trunks of the hypogastric arteries. After injection, specimens preserving the dural sac were obtained an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Our results also have implications for the anatomic understanding of the arterial cruciate anastamosis (arterial basket) of the conus medullaris and its associated variations and watershed zones. [15][16][17] As previously noted, the caudal ASA diminishes in caliber and branches into 2 small lateral branches, which curve dorsally and anastamose with the paired PSAs. In the study conducted by Rodriguez-Baeza et al (1991), 18 they noted that the AKA was accompanied by a posterior radiculomedullary artery in 63% of cases.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Our results also have implications for the anatomic understanding of the arterial cruciate anastamosis (arterial basket) of the conus medullaris and its associated variations and watershed zones. [15][16][17] As previously noted, the caudal ASA diminishes in caliber and branches into 2 small lateral branches, which curve dorsally and anastamose with the paired PSAs. In the study conducted by Rodriguez-Baeza et al (1991), 18 they noted that the AKA was accompanied by a posterior radiculomedullary artery in 63% of cases.…”
Section: Discussionmentioning
confidence: 57%
“…This finding contrasts with that of Lazorthes et al (1957), 19 who described a posterior radiculomedullary artery always associated with the AKA and Houdart et al (1965) 20 and Tveten (1976), 21 who noted that this association was found in only one-third of cases. As noted in these previous articles, 16,17 different configurations of the arterial basket have been identified. As our results indicate, the presence or absence of a GPRA correlates with different anastamotic configurations.…”
Section: Discussionmentioning
confidence: 87%
“…At their most distal extent, the anterior spinal artery and sulcal arteries are known to form the cruciate anastomosis of the conus medullaris of the spinal cord. However, this arterial basket represents the joining of the anterior and posterior spinal arteries and is rarely described as having an intraparenchymal component ( Rojas et al, 2018 ). Further, the medullary anastomosis described here represents a plausible anatomic basis for the infrequency of MMS, especially in regard to the anterior spinal artery territory.…”
Section: Discussionmentioning
confidence: 99%
“…Some arteries of this pial network, also termed “vasocorona,” communicate both longitudinal posterior pathways or, one of them with the anterior pathway, forming true anastomoses. Although the main anastomosis between the anterior and posterior anastomotic pathways is the arterial basket of the conus medullaris (Rojas, Ortega, & Rodríguez‐Baeza, 2018a), communications at the vasacorona level may have functional relevance in certain circumstances, at least locally. The pial collaterals may also extend to the neighboring spinal segments, forming accessory longitudinal anastomoses (Lasjaunias, Vallee, Person, Ter Brugge, & Chiu, 1985; Parke, Settles, Bunger, Whalen, & Said, 1999).…”
Section: Introductionmentioning
confidence: 99%